1997
DOI: 10.2307/2266140
|View full text |Cite
|
Sign up to set email alerts
|

Pollinator Limitation of Cytisus Scoparius (Scotch Broom), an Invasive Exotic Shrub

Abstract: Introductions of exotic species provide unique opportunities to study the demographic significance of species interactions, but as yet there is little information on how mutualistic interactions affect the invasion process. A shortage of mutualists could potentially limit the rate of population growth for an invading species. The introduced shrub Cytisus scoparius (Scotch broom, Leguminosae) is a pest plant on the west coast of North America. It produces flowers that are ''tripped'' open when pollinated and ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
258
3
17

Year Published

2001
2001
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(289 citation statements)
references
References 60 publications
(81 reference statements)
11
258
3
17
Order By: Relevance
“…Flowering plants that are introduced to new habitats not only must survive under potentially different environmental conditions, but also must be successfully pollinated by potentially new pollinator species, particularly if they are outcrossing annuals. The abundance of effective pollinators in the new habitat and the ability to adapt to new pollinators could affect a plant species' ability to persist and spread (Parker 1997;Richardson et al 2000).…”
Section: O Rganisms Colonizing New Environments Likely Facementioning
confidence: 99%
“…Flowering plants that are introduced to new habitats not only must survive under potentially different environmental conditions, but also must be successfully pollinated by potentially new pollinator species, particularly if they are outcrossing annuals. The abundance of effective pollinators in the new habitat and the ability to adapt to new pollinators could affect a plant species' ability to persist and spread (Parker 1997;Richardson et al 2000).…”
Section: O Rganisms Colonizing New Environments Likely Facementioning
confidence: 99%
“…While agamospermy and selfing may permit the transmission of favourable genes to new generations and more distant sites, thus facilitating local adaptation (Jain, 1976), clonality allows for immediate spatial occupation (Pyšek, 1997). Furthermore, since pollinator limitation can impede outcrossing plants (Parker, 1997), uniparental reproductive modes and generalist pollination are expected to help establish an invader from a small number of introduced individuals (Baker, 1955(Baker, , 1986Roy, 1990). Such reproductive alternatives can thus increase the probability that an introduced plant will successfully establish (Brown and Burdon, 1987).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, Parker (1997) found that strong pollination limitation of seed production in the invasive weed Cytisus scoparius did affect recruitment: costs of reproduction in this species were not strong enough to cancel out the value of extra seed production. Interestingly, populations of C. scoparius that experienced stronger pollination deficits had higher growth rates and were more invasive than those populations where pollinators were more abundant.…”
Section: Putting Pollination Deficits Into the Context Of Plant Life mentioning
confidence: 76%
“…This is most important in long-lived perennials, because increased fecundity may incur costs of reproduction that counteract potential gains. Very few studies have explicitly tied pollination limitation to population trajectories (Bierzychudek 1982, Calvo 1993, Ehrlén and Eriksson 1995, Parker 1997, and these studies present a complicated picture. Ehrlén and Eriksson (1995) found that supplementally pollinated plants of Lathyrus verna increased their seed production by 3.1 times, but then shrank in size, made fewer flowers the next year, and were more likely to enter dormancy than were controls.…”
Section: Putting Pollination Deficits Into the Context Of Plant Life mentioning
confidence: 99%